Loss of GATA4 C-Terminus by p.S335X Mutation Modulates Coronary Artery Vascular Smooth Muscle Cell Phenotype - Ting-Yan Yu; Xin-Xin Chen; Qing-Wen Liu; Fang-Fang Ma; Hong-Lang Huang; Lei Zhou; Wei Zhang (Mediators of Inflammation)
Coronary artery disease (CAD) has been the leading cause of morbidity and mortality worldwide, and its pathogenesis is closely related with the proliferation and migration of vascular smooth muscle cell (VSMC). We previously reported a truncated GATA4 protein lacking C-terminus induced by p.S335X mutation in cardiomyocyte from ventricular septal defect (VSD) patients. However, it is still unclear whether GATA4 p.S335X mutation could influence the development of CAD. GATA4 wild-type (WT) and p.S335X mutant (MU) overexpression plasmids were constructed and transfected transiently into rat coronary artery smooth muscle cell (RCSMC) to observe the proliferative and migratory abilities by MTS and wound healing assay, respectively. PCR array was used to preliminarily detect the expression of phenotypic modulation-related genes, and QRT-PCR was then carried out to verify the screened differentially expressed genes (DEGs). The results showed that, when stimulated by fetal bovine serum (10%) for 24 h or tumor necrosis factor-α (10 or 30 ng/ml) for 10 or 24 h, deletion of GATA4 C-terminus by p.S335X mutation in GATA4 enhanced the proliferation of RCSMC, without alteration of the migration capability. Twelve DEGs, including Fas, Hbegf, Itga5, Aimp1, Cxcl1, Il15, Il2rg, Il7, Tnfsf10, Il1r1, Irak1, and Tlr3, were screened and identified as phenotypic modulation-related genes. Our data might be beneficial for further exploration regarding the mechanisms of GATA4 p.S335X mutation on the phenotypic modulation of coronary VSMC.